Komunikasi Interpersonal Antara Driver Dan Pelanggan Go-Car Di Kota Surabaya - Sani, Lutfi Khairil; Putro, Raden Hartopo Eko (Soetomo Communication and Humanities, 2021)
The study aimed to identify what the interpersonal communication between drivers in interlace Go-Car to customers in Surabaya. This study using methods the qualitative study, case study As for data collection techniques using a technique researchers conducted in-depth interviews with various sources, observation, field and see the documents associated. The informant in this research as many as six people consists of four people a driver and two customers Go-Car. But, the research results show that interpersonal communication to passengers from the driver Go-Car had gone well and includes 5 effectiveness, openness in the form of interpersonal communication, empathy, the support, positiveness, and equality. But, in the interpersonal communication process of Go-Car drivers against passengers have some such obstacles to the driver sides that often become barriers in communicating. Then customers Go-Car felt as a whole are satisfied with the service provided Go-Car driver. Keywords: Communication, Interpersonal Communication, and Go-Car Driver.